2012
DOI: 10.1177/1553350612441863
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Splenectomy and Esophagogastric Devascularization Is a Safe, Effective, Minimally Invasive Alternative for the Treatment of Portal Hypertension With Refractory Variceal Bleeding

Abstract: Open splenectomy and esophagogastric devascularization (OSED) is a typical surgery for portal hypertension. Because of the high morbidity associated with it, it is desirable to develop a minimally invasive alternative. To investigate the safety and effect of laparoscopic splenectomy and esophagogastric devascularization (LSED), we performed LSED for 24 patients suffering from portal hypertension with refractory variceal bleeding while conducting OSED for 30 patients. The perioperative data and follow-up result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…In addition, Zhou et al, 22 Zhu et al, 24 Zheng et al 30 and Luo et al 31 investigated the effect of LS and OS procedures on liver function and found that the increases of aspartate aminotransferase, alanine aminotransferase, total bilirubin and direct bilirubin after surgery were significantly lower in LS group, which indicated minor liver function impairment.…”
Section: Comparisons Between Laparoscopic and Open Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Zhou et al, 22 Zhu et al, 24 Zheng et al 30 and Luo et al 31 investigated the effect of LS and OS procedures on liver function and found that the increases of aspartate aminotransferase, alanine aminotransferase, total bilirubin and direct bilirubin after surgery were significantly lower in LS group, which indicated minor liver function impairment.…”
Section: Comparisons Between Laparoscopic and Open Proceduresmentioning
confidence: 99%
“…Seven studies were identified with comparisons between laparoscopic and open procedures (four comparisons of LS with OS 20,22,24,32 and four comparisons of LSD with OSD [29][30][31][32] ). The main outcome measures reported are seen in Table 5.…”
Section: Comparisons Between Laparoscopic and Open Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…These techniques include the use of cumbersome intracorporeal bags to draw massively enlarged spleens, creation of enlarged incisions to morcellate and draw splenic issues, and hand-assisted laparoscopy. [1][2][3][4][5][6][7][8][9][10] Because of the poor condition of patients with these diseases and the potential for development of many perioperative complications, incisions impairment of the techniques should be controlled. Here, we report LSD with a new technique that greatly reduces impairments.…”
Section: Introductionmentioning
confidence: 99%